2010
DOI: 10.1021/es102046n
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient and Oxygen Concentrations within the Sediments of an Alaskan Beach Polluted with the Exxon Valdez Oil Spill

Abstract: Measurements of the background concentrations of nutrients, dissolved oxygen (DO), and salinity were obtained from a beach that has oil from the Exxon Valdez oil spill in 1989. Two transects were set across the beach, one passed through an oil patch while the other transect was clean. Three pits were dug in each transect, and they ranged in depth from 0.9 to 1.5 m. The DO was around 1.0 mg L(-1) at oiled pits and larger than 5 mg L(-1) at clean pits. The average nutrient concentrations in the beach were 0.39 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 25 publications
2
41
0
Order By: Relevance
“…Field studies in contaminated marshes and beach sediments, have demonstrated a wide range of biodegradation rates; oil biodegraded almost completely within a few weeks at some locations while it persisted for tens of years at other locations (Reddy et al, 2002;Short et al, 2004). Boufadel et al, (2010) noted low oxygen and nutrient concentration that might have prevented effective biodegradation of the Exxon Valdez oil spill. The study of Li and Boufadel (2010) highlighted that understanding beach hydraulics is a critical step in predicting the fate of oil within beaches.…”
Section: Longer-term Processesmentioning
confidence: 99%
“…Field studies in contaminated marshes and beach sediments, have demonstrated a wide range of biodegradation rates; oil biodegraded almost completely within a few weeks at some locations while it persisted for tens of years at other locations (Reddy et al, 2002;Short et al, 2004). Boufadel et al, (2010) noted low oxygen and nutrient concentration that might have prevented effective biodegradation of the Exxon Valdez oil spill. The study of Li and Boufadel (2010) highlighted that understanding beach hydraulics is a critical step in predicting the fate of oil within beaches.…”
Section: Longer-term Processesmentioning
confidence: 99%
“…They also found that oil is present in the transect with the smaller fresh groundwater flow (flowing seaward). Boufadel et al (2010) and Sharifi et al (2010) confirmed the presence of low concentration of oxygen and nutrients which thus could be the limiting factor for oil biodegradation. Taylor and Reimer (2008) reported that sites with the most extensive visibly recorded subsurface oil residues were on Smith Island, Knight Island, and Eleanor Island.…”
Section: Introductionmentioning
confidence: 78%
“…Robinson et al (2007bRobinson et al ( , 2009) and Li et al (2004) introduced that USP is not only an active mixing zone with a relatively fast flow rate and short seawater residence time but also an oxygen-rich zone that enhances the biodegradation rate of pollutants. The importance of oxygen concentration on biodegradation and hydrodynamic behaviors in coastal aquifer systems had been reported by Boufadel et al (2010) and Geng et al (2015).…”
Section: Introductionmentioning
confidence: 84%